Study of the influence of parameters of atmospheric perturbations on waves, flows, and the process of transformation of a contamination of various initial sizes in the Sea of Azov - Ivanov, V.A.; Cherkesov, L.V.; Shul’ga, T.Ya. (Reports of the National Academy of Sciences of Ukraine, 2014)
The results of simulation of the influence of winds of zonal directions (north-western, western, and south-western), which are homogeneous in space and time, on flows and waves in the Sea of Azov are presented. The analysis of the physical regularities of the propagation of a passive admixture of various initial areas in the Sea of Azov is executed with regard for the stationary flows.